2013
DOI: 10.1002/lary.24169
|View full text |Cite
|
Sign up to set email alerts
|

Otologic assessment of blast and nonblast injury in returning middle east‐deployed service members

Abstract: Due to its violent nature, blast exposure causes greater neuro-otological manifestations and deserves prompt otologic evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 14 publications
0
20
1
1
Order By: Relevance
“…While the prevalence of tinnitus normally increases with age, noise exposure is believed to be the most common cause of tinnitus in humans (Cooper, 1994). The prevalence of tinnitus is increased by several-fold among military populations, especially those who have served in battle zones (Shah et al, 2014). A recent study analyzed the incidence of hearing loss and tinnitus in a group of people who work in a noisy environment and found that approximately 40% of them had tinnitus (Hong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While the prevalence of tinnitus normally increases with age, noise exposure is believed to be the most common cause of tinnitus in humans (Cooper, 1994). The prevalence of tinnitus is increased by several-fold among military populations, especially those who have served in battle zones (Shah et al, 2014). A recent study analyzed the incidence of hearing loss and tinnitus in a group of people who work in a noisy environment and found that approximately 40% of them had tinnitus (Hong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Most reports have been directed at small samples involving civilian personnel. Several studies have reported minimal sensorineural hearing loss in blast-exposed individuals [5][6][7][8][9]25]; however, reversible conductive hearing losses have been more consistently identified. The greatest source of information on symptoms immediately following primary blast injury of the ear may be found in civilian literature [26].…”
Section: Introductionmentioning
confidence: 99%
“…It can develop after PBI or SBI with the effect of direct pressure. Therefore, it should be known that inner ear damage could accompany conductive hearing loss in some cases (9). In a recently conducted study, it was hypoth- esized that tympanic membrane perforation that could develop due to explosion could lead to deviations in the pressure wave, and it could form a protective mechanism over the inner ear.…”
Section: Discussionmentioning
confidence: 99%